The Effects of Ristocetin and von Willebrand Factor on Platelet Electrophoretic Mobility - Coller, Barry S. (1978)
Ristocetin will induce the agglutination of platelets in the presence of von Willebrand factor. In previous studies, an electrostatic mechanism was proposed for this phenomenon wherein first the platelet's surface charge is reduced by the binding of ristocetin and then the von Willebrand factor acts as a bridge between platelets. To test this hypothesis, the effects of ristocetin and von Willebrand factor, singly and together, on the electrophoretic mobility of normal, trypsinized, and Bernard-Soulier platelets was measured. Ristocetin alone, at concentrations of 0.5 mg/ml or more, produced a statistically significant reduction in the electrophoretic mobility of fresh or fixed platelets. Control experiments showed that the reduction was not due to changes in the ionic milieu of the solution. Therefore, the decrease in platelet mobility is evidence for binding of ristocetin to the platelet surface. Bernard-Soulier and trypsinized platelets also had reductions in mobility with ristocetin, suggesting that ristocetin binds to the platelet at sites other than the binding site for von Willebrand factor. The presence of plasma from a patient with von Willebrand's disease did not alter the reduction in mobility of normal platelets by ristocetin. However, the reduction was markedly enhanced in the presence of normal plasma. This enhancement did not occur with Bernard-Soulier platelets and was inhibited by anti-Factor VIII/von Willebrand factor antiserum or trypsinization of the platelets. Thus, the enhanced reduction appears to be associated with the binding of von Willebrand factor to the platelet surface. These studies indicate that platelets undergo two changes with ristocetin and von Willebrand factor, both of which facilitate agglutination: reduction in net surface charge and binding of von Willebrand factor, a large molecule which can serve as a bridge between platelets. In parallel studies, bovine von Willebrand factor, without ristocetin, agglutinated and reduced the electrophoretic mobility of normal but not Bernard-Soulier or trypsinized platelets; this indicates a similar mechanism of agglutination.